The 3-D shallow velocity structure and sedimentary structure of 2017 Ms6.6 Jinghe earthquake source area derived from dense array observations of ambient noise - Zhou, Ming; Tian, Xiaofeng; Yang, Zhuoxin; Liu, Qiaoxia; Gao, Zhanyong (Frontiers in Earth Science, 2023)
To deepen our understanding of the shallow structure and complex sedimentary environment of the Jinghe Ms6.6 earthquake area, a three-dimensional S-wave velocity structure model of 0–4 km was constructed based on ambient noise tomography with one mouth continuous seismic data recorded from a short period dense seismic array. The shear wave velocity model results from 0.5–4 km depths have shown that the shallow crustal medium has pronounced transverse heterogeneity and longitudinal stratification, and the velocity structure anomaly has strong correlation with the complex sedimentary structure near the surface. From near the surface to the deeper regions, the shear velocity maps have shown clear lateral variations and vertical variation which strongly correlate with the main geological structures and tectonic units in the study regions. Low shear-wave velocity has been shown throughout most of the Jinghe depression, whereas the Borokonu Mountains show high velocity. The thickness of Cenozoic sedimentary basement in the study area is approximately 1–4 km, and the distribution of thickness is highly uneven. The crystalline basement in the study area has strong bending deformation, and the non-uniform Cenozoic sediments are related to the strong bending deformation of the crystalline basement. The Kusongmuchik piedmont fault are high angle thrust faults cutting through the base. There are also many medium low angle faults, which do not penetrate the surface, which has indicated that they are in a concealed state at present. The results have provided a shallow high resolution 3D velocity model that can be used in the simulation of strong ground motion and for evaluating potential seismic hazards.